A residência multiprofissional na efetivação da integralidade na Atenção Básica à Saúde – uma revisão integrativa - Sousa, Geórgia Vieira (2023)
Reflecting on the relevance of training based on the multiprofessional residency offered by the Paulo Marcelo Martins Rodrigues School of Public Health in Ceará wasthe starting point of this research. The proposed objectives were to understand the importance of multiprofessional residency for the implementation of integrality in Primary Health Care (PHC), identifying the relationship between integrality and the actions of residents in primary care, encompassing the understanding of their trainingand professional practice. Texts and documents on the Unified Health System, the National Primary Health Care Policy, Primary Health Care, and Multiprofessional Residency were used to compose the theoretical framework. The methodology used was integrativa review, through the selection of articles that highlighted the importanceof multiprofessional residency for professional training and its contribution to strengthening health policy. The discussion on integrality in health goes beyond patient care, encompassing family and community care, with a focus on the multiprofessionaland interdisciplinary team. It is important to note that the need for a health- disease process is not only about bringing different professions together to provide care, but also about promoting integrality care through interdisciplinary approaches in theterritory. The results found can (and should) be applied in the practical implementation of PHC, as the improvement of access to services through the actions of multiprofessional residency strongly contributes to community adherence to consultations in Basic Health Units and in the Health Care Network, as well as empowering patients in their own health-disease process. The scientific contribution presented in this study refers to the collaboration that multiprofessional residency promotes in the effective implementation of the principle of integrality proposed by theUnified Health System. Promoting health through interdisciplinary work is affirmed as an important strategy to propose a shift from the biomedical model to the biopsychosocial model.